Karakteristik dan Jenis Kesulitan Belajar Anak Slow Learner - Wachyu Amelia (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2016)
Children with special needs (ABK) is that they are hampered by physical, cognitive, and social in developing their maximum potential. This study aims to determine the characteristics and learning difficulties slow learner child. The method used in this research is descriptive method with cross sectional approach. Sample was taken by purposive sampling. The results showed that out of 33 respondents, the proportion of the most experienced slow learner is in the age group 15-16 years (51.5%), male gender (66.7%), father's occupation is Labor (57.6 %), education is the father of junior high (39.4%) and the mother's education, namely junior high (45.5% and has a brother numbered 2 (66.7%). This type of disorder found in children as the low capability of understanding (66.7 %). Slow in doing academic work (66.7%), learning achievement is very low (66.7%), while children who grade (75.7) and were failing a grade (24.3%).Keywords : special needs children, slow learner, characteristics, learning difficulties